Pengaruh Potongan Harga, E-Word Of Mouth, Dan Kepercayaan Terhadap Minat Beli Pada Sociolla Di Banjarmasin - Priti Salwa Ramadhanti; Muhammad Hasanur Arifin; Rizki Muslim Hidayat (Business Administration, FISIP ULM, 2022)
This study aims to examine the effect of Price Discounts, E-Word of Mouth, and Trust on Interest in Buying Sociolla in Banjarmasin. This study uses a quantitative method with a sampling technique using a non-probability sampling technique, namely purposive sampling, the data collection method is a questionnaire through a gform. the sample in this study amounted to 140 respondents. Data analysis using multiple linear regression and data processing using SPSS 25 software.The results of this study are partially discounted prices have no significant effect on Purchase Interest of Sociolla in Banjarmasin, while E-Word of Mouth and Trust partially have a significant effect on Buying Interest of Sociolla in Banjarmasin. This study also shows that simultaneously Discounts, E-Word of Mouth, and Trust have a significant effect on Buying Interest of Sociolla in Banjarmasin